Coconut-based cropping system keeps farmers cheerful - Basavaraju, T B; Maheswarappa, H P; Nath, J C; Khandekhar, R G; Rajkumar, D; Janakiram, T (Indian Horticulture, 2019)
The coconut palms are generally planted at a wider spacing due to their morphological features. The crop does not fully utilize the basic natural resources such as soil and sunlight available in the garden due to its rooting pattern and canopy structure. The effective root zone of the adult bearing palm is confined laterally within a radius of 2 m around the base of the palm and majority of the roots are found between 30 and 120 cm depth from the surface. The structure and orientation of coconut leaves permit more than 50 per cent of solar radiation incident on crown to penetrate to lower levels. The under-utilized soil space and solar radiation in monocrop stands can be utilized by growing crops having different stature, canopy shape and size, and rooting habits. Such crop combinations intercept and utilize light at different vertical intervals and forage soil at different layers maximizing biomass production per unit area of land, time and inputs. Recently, farmers are experiencing the non-profitability of coconut cultivation due to fluctuating prices of coconut and increasing incidence of pests and diseases in addition to low/erratic rainfall. Hence, there is a need for crop diversification and intensification with compatible crops to increase the productivity and income by effective and efficient utilization of soil space and solar radiation.